PENGELOLAAN WISATA RELIGI MAKAM TROLOYO DAN DAMPAKNYA TERHADAP KEHIDUPAN SOSIAL-EKONOMI MASYARAKAT LOKAL - rakhmawati, liyana; setyawan, wahyu aris (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2020)
ABSTRACT Rahmawati , Liyana. 2020. Management of Tourism ReIegi Tomb Troloyo and Socio-Economic Impact on Local Communities Life. STAISAM pungging mojokerto. Keywords: Travel Management, Social-Economic Impact This reseaarch aims to know the management of religious tourism tomb Troloyo in Sidodadi Hamlet, Sentonorejo Village, Trowulan district in Mojokerto Regency, and to know the impact of the management of religious tourism tomb Troloyo towards the socio-economic life of local communities. Data collection methods used in this study is the observation, interviews, and documentation. The data analysis technique used is descriptive exploratory method that aims to describe and summarize the management of religious tourism tomb Troloyo and its impact on socio-economic life of local communities. The results of this research can be know by: (1) in the term of management, the managers of tomb Troloyo religious tourism commit the cooperation with the form of MoU (Memorandum of understanding) between the district government and village government. Physical infrastructure has increased 100 % from the previous condition. (2) from the management of tomb Troloyo, it brings the impact on social-economic life such as the pattern of a society that tends to be consumptive, an emphasis on safety and order, the changes in the education sector, and the price of land in the area of tomb which tend to be expensive, life of the local community is the change of livelihoods, occurred the absorption employments that create a new jobs, and the increasing income of local communities is seen from the increasing percentage of local community income that is 70,3 %.